Recent advances in Immunobullous diseases - Bhari, N; Verma, K K (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
The researches in the recent past have led to better understanding of pathogenesis, diagnostic methods and treatment of autoimmune bullous diseases. Significant advances in our understanding of pathogenesis of pemphigus have resulted in development of multiple pathogenic models and discovery of new signalling pathways involved in its pathogenesis. Various newer clinical variants have been described and diagnostic methods have been developed. Disease activity scoring methods in pemphigus provide comparable and interpretable results which facilitate better understanding of disease activity and assessment of treatment response. Use of biological agents have led to better control of disease activity and other newer therapeutic options are being explored. NJDVL Vol. 13, No. 1, 2015 Page: 1-11